On the performance of multi-GPU-based expert systems for acoustic localization involving massive microphone arrays. Issue 13 (1st August 2015) - Belloch, Jose A.; Gonzalez, Alberto; Vidal, Antonio M.; Cobos, Maximo
Highlights Expert system for passive sound source localization that makes use of multiple GPUs. Fine spatial grids and a high number of microphones provide excellent localization. GPU resources for managing a large expert system are described. A complete set of simulations evaluates the performance of the expert system. Excellent localization accuracy is achieved even in adverse environments.